Clinical social work practice a cognitive-integrative perspective - Berlin, Sharon B. (New York ; Oxford : Oxford University Press, 2002)
This text presents a cognitive perspective on social work clinical practice that emphasises the role of the environment in shaping personal meaning. This perspective combines cognitive psychology's internal focus on how people think about themselves with a look outwards.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychiatric social work -- United States; Cognitive therapy -- United States